Individual Variation in Dietary Wariness Is Predicted by Head Color in a Specialist Feeder, the Gouldian Finch - Georgina R. Eccles (Frontiers Media S.A., 2021)
Shifts in resource availability due to environmental change are increasingly confronting animals with unfamiliar food types. Species that can rapidly accept new food types may be better adapted to ecological change. Intuitively, dietary generalists are expected to accept new food types when resources change, while dietary specialists would be more averse to adopting novel food. However, most studies investigating changes in dietary breadth focus on generalist species and do not delve into potential individual predictors of dietary wariness and the social factors modulating these responses. We investigated dietary wariness in the Gouldian finch, a dietary specialist, that is expected to avoid novel food. This species occurs in two main head colors (red, black), which signal personality in other contexts. We measured their initial neophobic responses (approach attempts before first feed and latency to first feed) and willingness to incorporate novel food into their diet (frequency of feeding on novel food after first feed). Birds were tested in same-sex pairs in same and different head color pairings balanced across experiments 1 and 2. Familiar and novel food (familiar food dyed) were presented simultaneously across 5 days for 3 h, each. Gouldian finches fed on the familiar food first demonstrating food neophobia, and these latencies were repeatable. Birds made more approach attempts before feeding on novel than familiar food, particularly red-headed birds in experiment 1 and when partnered with a black-headed bird. Individuals consistently differed in their rate of incorporation of novel food, with clear differences between head colors; red-headed birds increased their feeding visits to novel food across experimentation equaling their familiar food intake by day five, while black-headed birds continually favored familiar food. Results suggest consistent among individual differences in response to novel food with red-headed birds being adventurous consumers and black-headed birds dietary conservatives. The differences in food acceptance aligned with responses to novel environments on the individual level (found in an earlier study) providing individuals with an adaptive combination of novelty responses across contexts in line with potential differences in movement patterns. Taken together, these novelty responses could aid in population persistence when faced with environmental changes.